Wave propagation and soliton solutions of the Allen-Cahn model - Tariq, Kalim U. U.; Zubair, Muhammad; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2023)
The Allen-Cahn equation (ACE), which has applications in solid-state physics, imaging, plasma physics, material science and other fields, is one of the most important models of the modern era for describing the dynamics of oil pollution, reaction-diffusion mechanisms, and the mechanics of crystalline solids. By using the ( 1 G & PRIME;)-expansion method (GEM) and the Bernoulli sub-ODE schemes, some new traveling wave solutions for the governing model are created in this study (BSODE). The reduced integrable ordinary differential equation is produced using the traveling wave hypothesis. To better understand their behavior, the 3D, contour, and 2D graphs are displayed for a number of fascinating exact solutions. Additionally, we use numerical simulation to confirm the stability of the derived analytical solutions. It results the propagation of temporal soliton for long time of simulation. These results will be used to explain physical phenomenon in crystalline solids and others fields.
Keywords: The Allen-Cahn model; traveling waves solutions; fluid dynamics; analytical solutions; nonlinear evolution models